Osimertinib: a breakthrough for the treatment of epidermal growth factor receptor mutant lung adenocarcinoma - Karachaliou, Niki; Barron, eliciano Barron; Viteri, Santiago; Molina, Miguel Angel; Rosell, Rafael (Translational Cancer Research, 2017)
At the time of acquired resistance to the first generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs), gefitinib, erlotinib or afatinib (1), 50–60% of EGFR mutant non-small cell lung cancer (NSCLC) patients have developed the secondary gatekeeper T790M point mutation on exon 20 of the EGFR gene (2,3). Osimertinib (AZD9291) is a third-generation EGFR TKI that targets EGFR mutant (including T790M positive) tumors (4). It was initially evaluated in EGFR mutant NSCLC patients who had disease progression after previous treatment with an EGFR TKI, in the phase I part of the phase I/II AURA study (5). A response rate of 51% was achieved for all patients treated across all dose levels. Among the 222 patients of the expansion cohorts, the response rate to osimertinib was 61% for EGFR T790M-positive patients while the EGFR T790M-negative patients were not able to achieve a response rate greater than 21% (Table 1). No dose limiting toxicities were observed at any dose level and, based on tumor growth inhibition, the dose of 80 mg once daily was selected for being further evaluated for the treatment of EGFR T790M-positive NSCLC patients (5). On November 13th 2015, and on February 3rd 2016, FDA and EMA approved osimertinib 80 mg once daily for the treatment of EGFR T790M-positive NSCLC patients, respectively, based on the data from two phase II studies (AURA extension and AURA2) and the AURA phase I expansion study. Sixty-three EGFR T790M-positive, dose expansion cohort patients receiving 80 mg of osimertinib once daily in the phase I part of the AURA study demonstrated an objective response rate (ORR) of 71% [95% confidence interval (CI), 57–82] and a median progression-free survival (PFS) of 9.7 months (95% CI, 8.3–13.6). In a pre-planned pooled analysis of the AURA extension phase II study and the AURA2 phase II study with a total of 411 EGFR T790M-positive patients, ORR was 66% and median PFS was 11.0 months (95% CI, 9.6–12.4) (6).